DEVELOPMENT BANK: KEY TO SECTOR IMPROVEMENT - Bortesi Longhi, Luis (2016)
A preliminary concept of great importance lies in the necessary distinction between economic growth and development in general. Indeed, growth is exclusively circumscribed to the economic aspect, it is only quantitative in nature and its main macroeconomic record lies in the measurement of gross domestic product. Development, on the other hand, is not limited exclusively to the economic aspect and is not purely quantitative, since it encompasses qualitative aspects that also include economic, political, social and cultural fields.In the present article, different aspects of the various economic systems are outlined, particularly analyzing Peru; according to the 58th article of the current constitution, it responds to the Social Market Economy model.Thus, within the whole context, the analysis concentrates on the study of the virtues and favorable consequences, with the institution of sectoral development banking.